Incremento en la expresión del ARNm del receptor c-Met en el cáncer gástrico. - Amemiya, Hideki; Peña, Alix; Chiurillo, Miguel; Moscoso, Jaime; Useche, Alejandro; Baffi, Raúl (Investigación Clínica, 2013)
Ver resumen pdf.